Implementasi Buku Materi Bahasa Arab-Inggris dalam Pembelajaran Bahasa pada Anak Usia Dini Kelompok A di KB-RA. Perwanida Ketintang Surabaya - Alfian Nuril Laily Abror; Imam Syafi'i; Irfan Tamwifi (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2021)
This study aims to describe the implementation, the strengths and the weaknesses of Arabic-English textbooks in language learning in early childhood group A in KB-RA. Perwanida Ketintang Surabaya. The results show that the implementation of outdoor learning. Students are asked to listen and pay attention to the teacher when exemplifying the vocabulary or sentences being studied. Students are able to focus and give respond to the explanations when the teacher gives questions to all students, students answer the teacher's questions together using Arabic or English. These activities are carried out repeatedly. Then, the teacher asks one of the students randomly to do reinforcement by asking students about the language learned today. The advantages of Arabic-English textbooks are as follows: students are able to explore their vocabularies or sentences in Arabic and English, able to increase children's motivation to learn, contain interesting learning materials, make it easy for teachers. This book is prepared based on the needs of early childhood, contains interesting illustrations, based on linguistic aspects and contains the materials that are taught, namely Arabic and English. While the weakness of this book is that there is no written evaluation/assessment for students, how to present the book is not completed with media, students cannot repeat learning the material at home using this book and some students still have lack focus when having classes